2019
DOI: 10.1111/all.13749
|View full text |Cite
|
Sign up to set email alerts
|

EAACI Guidelines on Allergen Immunotherapy: House dust mite‐driven allergic asthma

Abstract: blind placebo controlled; EAACI, European Academy of Allergy and Clinical Immunology; FEF 25-75, forced expiratory flow at 25-75% of the pulmonary volume; FEV1, forced expiratory volume in 1 second; GINA, Global Initiative for Asthma; GRADE, The Grading of Recommendations Assessment, Development and Evaluation; HCP, healthcare professional; HDM, house dust mites; ICS, inhaled corticosteroids; MEF 25, maximal expiratory flow at 25% of forced vital capacity; MEF 50, maximal expiratory flow at 50% of forced vital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
217
0
25

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(245 citation statements)
references
References 94 publications
3
217
0
25
Order By: Relevance
“…The most important meta‐analyses (with their intrinsic limitations) suggested that AIT, and SLIT, are clinically effective in reducing asthma symptoms and medication score, without an increase in adverse events. It has to be considered that asthma is more frequent in mite‐sensitized patients, where it is more difficult to assess the exposure and to evaluate outcomes (Table ). During the last decade, some SLIT studies were designed specifically for asthma, taking into account the exacerbation rate and/or the use of inhaled corticosteroids .…”
Section: The Recent History Of Slitmentioning
confidence: 99%
“…The most important meta‐analyses (with their intrinsic limitations) suggested that AIT, and SLIT, are clinically effective in reducing asthma symptoms and medication score, without an increase in adverse events. It has to be considered that asthma is more frequent in mite‐sensitized patients, where it is more difficult to assess the exposure and to evaluate outcomes (Table ). During the last decade, some SLIT studies were designed specifically for asthma, taking into account the exacerbation rate and/or the use of inhaled corticosteroids .…”
Section: The Recent History Of Slitmentioning
confidence: 99%
“…Blo t 13 is the first HDM allergen to which a cross-reactivity with human proteins has been demonstrated; therefore, the probability that an autoreactive response to homologous proteins such as FABP3 and FABP4 could be induced during the course of an allergen immunotherapy (AIT) with HDM extract deserves evaluation. In some studies, immunologic diseases such as autoimmune diseases are considered a relative contraindication for AIT [31]. However, in a large nationwide study analyzing data over a decade, patients treated with AIT had lower incidence of autoimmunity compared to those on conventional treatment (nasal steroids and oral antihistamines) [32].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the recently published EAACI Guidelines on Allergen Immunotherapy for HDM-driven allergic asthma provided evidence-based practical recommendations on how optimally applying AIT in asthma. 8 Despite all the above, real-life data reveal that the use of AIT in asthma is at present very limited and evidence is still lacking on the role of AIT on several relevant asthma endpoints, such as the disease control and progression. Furthermore, the reported beneficial effect of AIT in childhood asthma has been recently questioned, based on studies performed in children not treated according to GINA guidelines.…”
Section: Allergen Immunotherapy For Asthma: Looking "Back To the Future"mentioning
confidence: 99%
“…As secondary outcomes, SCIT also improved quality of life and small airways function (assessed through FEF 25%‐75% values), as well as decreased specific airway hyperreactivity. Moreover, the recently published EAACI Guidelines on Allergen Immunotherapy for HDM‐driven allergic asthma provided evidence‐based practical recommendations on how optimally applying AIT in asthma …”
mentioning
confidence: 99%